SPM: split piecewise mapping for high quality wireless video delivery. (1st January 2012) - Lai, Wen-Ping; Fu, Wei-Hao
Multiple prioritised access category (AC) queues and virtual collision handling among them are the main mechanism of the IEEE 802.11e EDCA for multimedia service differentiation. However, the AC for video (AC_VI) is characteristic of FIFO, and thus its performance is limited. For further performance enhancement, differentiation among video packets can help. This study presents a novel cross-layer design combining the error propagation length (EPL) scheme in the application layer allowing each video frame in a group of pictures to have its own importance level, and our proposed split piecewise mapping (SPM) algorithm in the MAC layer offering a corresponding mapping probability function for each importance level of video packets among the AC queues. The results show that the proposed EPL+SPM design outperforms the existing ones, with largest achieved gains as high as 2.8 dB over I/P+PM, 4.1 dB over I/P+AM and 7.4 dB over EDCA.